Reviews (The Australian journal of anthropology, 1938)
Book reviewed in this article: Ein vorkapitalistisches Wirtschaftssystem in Buin. By Richard Thurnwald. Menschen der Sudsee: Charaktere und Schicksale. By Hilde Thurnwald. Australian Aboriginal Decorative Art. By Frederick D. McCarthy, with a Foreword by Professor A. P. Elkin.